2015
DOI: 10.4274/tdd.2722
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Superficial Fungal Infections in Children

Abstract: Amaç: Bu retrospektif çalışma ile pediatrik dermatoloji polikliniğine bir yıl içinde başvuran yüzeysel mantar enfeksiyonu olan 51 olgunun klinik değerlendirilmesi amaçlandı. The most common symptom was the pruritus. Thirty (58%) patients were treated with local antimycotics and 21 (42%) patients were treated with systemic terbinafine or itraconazole. Conclusion:In this study it was found that, tinea capitis was the most frequent form of dermatomycosis and onychomycosis in children are not uncommon as it is men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
4
2
0
Order By: Relevance
“…While Nanda et al (4) reported a ratio of 0.62% and Oke et al (9) reported a ratio of 4.4%, in our country Seraslan et al (10) detected a ratio of 5.4%, Tamer et al (12) detected a ratio of 0.09% and Kavak et al reported a ratio of 2.5% (18) and they all declared that the disease increased with age. In similarity to the trial by Ertas et al, we detected an overall ratio of 0.48% and 19% in 518 children (16). The increase observed with the increasing age was statistically significant.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…While Nanda et al (4) reported a ratio of 0.62% and Oke et al (9) reported a ratio of 4.4%, in our country Seraslan et al (10) detected a ratio of 5.4%, Tamer et al (12) detected a ratio of 0.09% and Kavak et al reported a ratio of 2.5% (18) and they all declared that the disease increased with age. In similarity to the trial by Ertas et al, we detected an overall ratio of 0.48% and 19% in 518 children (16). The increase observed with the increasing age was statistically significant.…”
Section: Discussionsupporting
confidence: 69%
“…Balci et al detected onychomycosis in a pediaric screening involving 8122 children between 5 and 16 years of age (0.018) (35). Ertas et al told a ratio of 17.8% (16). In this study, we detected an overall ratio of onychomycosis of 0.23%; the ratio was 9% among the fungal infections and the condition was most common between 12 and 16 years and occurred more among girls.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations